2002
DOI: 10.1007/s00520-002-0354-3
|View full text |Cite
|
Sign up to set email alerts
|

What do patients living with advanced cancer and their carers want to know? – A needs assessment

Abstract: Our primary objective was to determine the content and format that is most suitable for educational events targeting patients and carers who are living with advanced cancer. Secondary objectives included examining the differences in information needs between patients and their carers, and providing an estimate of the rate of participation in educational events targeting such patients and carers. Out-patients receiving palliative radiotherapy at Toronto Sunnybrook Regional Cancer Center and their carers were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0
20

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 29 publications
4
74
0
20
Order By: Relevance
“…The high proportion of patients reporting pain (92% of breast versus 75% of GI patients) and fatigue and weakness (58% versus 88%) reflects findings from other studies [36]. Gastrointestinal symptoms including diarrhoea, constipation, nausea and vomiting were also problematic for the majority of the participants (67% of breast versus 88% of GI patients).…”
Section: Discussionsupporting
confidence: 64%
“…The high proportion of patients reporting pain (92% of breast versus 75% of GI patients) and fatigue and weakness (58% versus 88%) reflects findings from other studies [36]. Gastrointestinal symptoms including diarrhoea, constipation, nausea and vomiting were also problematic for the majority of the participants (67% of breast versus 88% of GI patients).…”
Section: Discussionsupporting
confidence: 64%
“…Within a given area, preferences for additional input might differ greatly according to the particular item of need. Taking the example of information seeking, Wong [39] found that needs varied from 14-75% according to the topic area, and this would seem to have important implications for targeted changes in information provision: some topics appear to be priority areas for immediate improvement (those for which most patients have unmet needs) but there is also an apparent necessity to individualise provision (there was no topic for which all respondents desired additional information -uniform increases in information provision might overwhelm patients for whom current provision is sufficient).…”
Section: Prevalence Of Unmet Needsmentioning
confidence: 99%
“…Information about the patient's disease trajectory, anticipated course of disease, and the range of emotions experienced by families helps normalize the experience and enhances a caregiver's sense of control. In Wong et al (2002) study, priority areas of information and education needs identified by cancer outpatients and their caregivers included management of pain, weakness, and fatigue, followed by the types of services available to facilitate patient care at home. Caregivers report learning most of their caregiving skills through trial and error and would like more assistance from the formal health care system (Given et al, 2001).…”
Section: Discussionmentioning
confidence: 99%